When Bigger is Better: The Impact of a Tiny Tick Size on Undercutting Behavior - Dyhrberg, Anne H.; Foley, Sean; Svec, Jiri (Journal of Financial and Quantitative Analysis, 2023)
Abstract Economically insignificant tick sizes encourage undercutting behavior, thus harming market quality. Theoretical work shows that increasing tick sizes in unconstrained markets reduces undercutting and improves market quality. Equity market pricing grids are generally too coarse to test this prediction. We examine a cryptocurrency market with infinitesimal tick sizes where undercutting limit orders acquire price priority without meaningful economic cost. We show that increasing tick sizes reduces undercutting behavior, increases liquidity provision and quoted depth, and reduces transaction costs for institutional and retail-sized trades while decreasing short-term volatility. Tiny tick sizes are suboptimal, supporting increased minimum trading increments in tick-unconstrained markets.